1996
DOI: 10.1093/jac/37.6.1091
|View full text |Cite
|
Sign up to set email alerts
|

Effect of growth conditions on antimicrobial activity of DU-6859a and its bactericidal activity determined by the killing curve method

Abstract: The effect of growth conditions on the antibacterial activity of DU-6859a against Staphylococcus auerus, Escherichia coli, and Pseudomonas aeruginosa was compared with those of levofloxacin, sparfloxacin, and ciprofloxacin. This activity was not affected by different media, inoculum size or the addition of human serum, but was decreased under acidic conditions, in human urine, and in the presence of magnesium and ferrous ion, as were the other quinolones tested. Time-kill curve studies demonstrated the bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…The MICs and minimal chlamydiacidal concentrations of sitafloxacin for various species of chlamydia ranged from 0.031 to 0.125 g/ml. Sitafloxacin had an excellent therapeutic effect on experimental Chlamydia psittaci pneumonia and was more potent than tosufloxacin, ofloxacin, and ciproflxacin, although slightly less potent than sparfloxacin.Sitafloxacin is a new fluoroquinolone antimicrobial agent, which has been reported to have a broader spectrum and more potent activity against gram-positive and gram-negative bacteria than currently available quinolones such as ofloxacin, ciprofloxacin, tosufloxacin, and sparfloxacin (11,15,17). In a preliminary study (12), sitafloxacin showed good clinical efficacy against pneumonia and chronic respiratory tract infection.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The MICs and minimal chlamydiacidal concentrations of sitafloxacin for various species of chlamydia ranged from 0.031 to 0.125 g/ml. Sitafloxacin had an excellent therapeutic effect on experimental Chlamydia psittaci pneumonia and was more potent than tosufloxacin, ofloxacin, and ciproflxacin, although slightly less potent than sparfloxacin.Sitafloxacin is a new fluoroquinolone antimicrobial agent, which has been reported to have a broader spectrum and more potent activity against gram-positive and gram-negative bacteria than currently available quinolones such as ofloxacin, ciprofloxacin, tosufloxacin, and sparfloxacin (11,15,17). In a preliminary study (12), sitafloxacin showed good clinical efficacy against pneumonia and chronic respiratory tract infection.…”
mentioning
confidence: 99%
“…Sitafloxacin is a new fluoroquinolone antimicrobial agent, which has been reported to have a broader spectrum and more potent activity against gram-positive and gram-negative bacteria than currently available quinolones such as ofloxacin, ciprofloxacin, tosufloxacin, and sparfloxacin (11,15,17). In a preliminary study (12), sitafloxacin showed good clinical efficacy against pneumonia and chronic respiratory tract infection.…”
mentioning
confidence: 99%
“…Similarly, saturable protein binding at higher doses should increase and not decrease influx clearance. However, perhaps those rabbits given the lowest grepafloxacin dose developed a more pronounced inflammation of the serum-CSF barrier than those given higher doses, which might have resulted in an increased passive diffusion clearance at the serum-CSF barrier (12,29). If increased inflammation at the lower dose increases average influx clearance, one could expect a decreased efflux clearance (in excess of the influx clearance), as inflammation can reduce bulk flow clearance (see above).…”
Section: Discussionmentioning
confidence: 99%
“…Antibacterial activity determination in liquid culture was carried out with different serial dilutions of KA in LB broth. Isolation of resistant strains was attempted as described by Tanaka et al [8]. The effect of KA during bacterial growth was studied following change in absorbance when different concentrations of the compound were added to a O.D.…”
Section: Methodsmentioning
confidence: 99%